PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN DI PT TLAGA SINGHA MANDALA GIANYAR - Ni Kadek Suciadnyani; I Putu Bagus Suthanaya; NLK Julyanti Paramita Sari (Universitas Triatma Mulya, 2023)
Employee performance is an important factor for the progress of an organization or company depending on the human resources it has. Optimal performance is needed in supporting the implementation of all the work that has been assigned. Performance is influenced by many factors such as work environment and communication. This study aims to determine the effect of the work environment and communication on employee performance. The location of this research is at PT. Tlaga Singha Mandala Gianyar. Data collection techniques used are observation, questionnaires, documentation and interviews. The population uses employees at PT. Tlaga Singha Mandala Gianyar, with a sample of 60 respondents. The data analysis technique used is Descriptive Statistical Analysis, Data Instrument Test, Classical Assumptions, Regression, F and t. Based on the results of the study, it was found that the work environment has a positive and significant influence on employee performance, communication has a positive and significant effect on employee performance and the quality of food and communication together have a significant effect on employee performance. Suggestions that can be given by researchers are that PT Tlaga Singha Mandala Gianyar routinely holds outing activities or other togetherness activities so that later the relations between employees run harmoniously, build harmonious relationships between employees and always become a mediator when conflicts occur between employees and provide training to improve skills employees at work